Sosialisasi Google Family Link: Upaya Penguatan Pengawasan Orang Tua di Kelurahan Sekargadung - Hakim, Lukman; Mecca, Aulia Inayah; Sa'diyah, Robi'atus; Faizin, Khoirul; Febyani, Reny; Wardani, Reri Ari; Aziz, Adi Nur (Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation has significantly altered parenting practices and introduced new challenges for parents, particularly in supervising children’s use of digital devices. Limited digital literacy among parents increases children’s vulnerability to negative impacts, such as excessive gadget use and exposure to inappropriate content. This community service activity was conducted in Sekargadung Subdistrict, Pasuruan City, with the objective of enhancing parents’ knowledge, skills, and awareness in utilizing the Google Family Link application as a tool to strengthen digital supervision of children. The activity employed a participatory educational approach through socialization sessions, including lectures, discussions, question-and-answer activities, and direct assistance in the installation and use of the application. The results indicate an improvement in parents’ understanding and engagement, although several technical challenges related to account management were still encountered. Overall, this activity underscores the importance of strengthening parents’ capacity to ensure that digital supervision is implemented effectively, educationally, and in support of healthy parenting practices in the digital era.